2010
DOI: 10.1149/1.3258274
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of LiCoO[sub 2] Cathodes in Lithium-Ion Batteries Using Surface Modification by Atomic Layer Deposition

Abstract: Ultrathin atomic layer deposition (ALD) coatings enhance the performance of lithium-ion batteries (LIBs). Previous studies have demonstrated that LiCoO2 cathode powders coated with metal oxides with thicknesses of ∼100 to 1000Å grown using wet chemical techniques improved LIB performance. In this study, LiCoO2 powders were coated with conformal Al2normalO3 ALD films with thicknesses of only ∼3 to 4Å established using two ALD cycles. The coated LiCoO2 powders exhibited a capacity retention of 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
281
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(294 citation statements)
references
References 57 publications
12
281
0
1
Order By: Relevance
“…[ 21,22] during the initial charge/discharge cycle is observed in Figure 2d. However, at higher numbers of charge-discharge cycles, all the Al 2 O 3 ALD coated LNMO electrodes exhibit much higher coulombic efficiencies than the bare LNMO electrodes do.…”
Section: Ex-situ Analysesmentioning
confidence: 99%
“…[ 21,22] during the initial charge/discharge cycle is observed in Figure 2d. However, at higher numbers of charge-discharge cycles, all the Al 2 O 3 ALD coated LNMO electrodes exhibit much higher coulombic efficiencies than the bare LNMO electrodes do.…”
Section: Ex-situ Analysesmentioning
confidence: 99%
“…While there has been a distinct move for alternative electrode hosts (LiCoO2 is both toxic and relatively expensive to produce), research has still considered a number of practical LiCoO2 architectures with high voltage and good rate performance [249][250][251][252][253][254][255][256][257]. In the interest of capacity retention, commercial LiCoO2 cells typically adopt a reversible capacity to 0.5 Li + by setting the upper-cut off potential to 4.2 V, thus yielding working capacities approaching 150 mA h g -1 [258].…”
Section: Licoo2mentioning
confidence: 99%
“…Limiting the occurrence of potentially poisonous interactions is therefore highly advantageous to the cycle life of the electrode. Recent studies have demonstrated nanometre-scale coatings of inactive Al2O3 on LiCoO2 nanoparticles [256,262,263]. In the first example, LiCoO2 particles prepared by a molten-salt synthesis using CoO, LiOH and KNO3, were subjected to consecutive ALD cycles, each depositing a thin-film of Al2O3 ranging between 1.1-2.2 Å in thickness.…”
Section: Licoo2mentioning
confidence: 99%
“…whose dimension is equal to the dimension of thermal capacitance, and nondimensional properties are compared: Fig.3 shows relative (nondimensional) thermal capacitances of bulk (b) and film-structure (f) subject to the relative temperature x, for It can be seen that in low-temperature region (Fig.4a) thermal capacitance of film is lower than that of massive specimens, whereas at the intermediate temperatures situation is reversed [5]. The intersection point of two curves at low temperatures is moving -with increase of film-thickness -towards lower temperatures (Fig.4a -> c).…”
Section: Thermodynamics Of Phonon Filmsmentioning
confidence: 99%
“…ALD requires only a minimum quantity of precursors and ALD coatings are compatible and provide control of atomic thickness. ALD could be a promising alternative manner for coating electrode materials for LIBs [5].…”
Section: Introductionmentioning
confidence: 99%